OP0282 New systemic sclerosis risk loci identified through a meta-gwas strategy. (12th June 2018) - López-Isac, E.; Acosta-Herrera, M.; Assassi, S.; Simeón, C.P.; Carreira, P.E.; Castellví, I.; Ortego-Centeno, N.; Beretta, L.; Lunardi, C.; Gabrielli, A.; Moroncini, G.; Hunzelmann, N.; et al.
Abstract : Background: In systemic sclerosis (SSc), previous GWASs have identified several loci associated with the disease, but their rate of discovery has been limited due to modest sample sizes. Extensive collaborative efforts have enabled us to gather the largest cohort of SSc patients. In the present study, we have performed a large meta-GWAS taking advantage of our well-powered cohort. Objectives: To continue unravelling the complex genetic component of SSc. Methods: The complete set of individuals enrolled for this study comprised a total of 26 679 genome-wide genotyped individuals of European ancestry. PLINK and EIGENSTRAT were used for quality control and population stratification adjustments. Genotype imputation was performed with IMPUTE2 and the 1000 Genome Project Phase 3 as reference panel. Results: Twenty-three loci reached the genome-wide significance level ( p -value<5×10–8) in our large-scale meta-analysis. Twelve out of the total significant signals represented new associations and involved novel pathways in the pathophysiology of the disease. Significant enrichment was observed for epigenetic marks of active promoters and active enhancers in critical cell types for the disease. In addition many of the interrogated variants correlated with eQTLs thus altering gene expression. Conclusions: Using a large meta-GWAS, we have identified twelve novel associations for SSc susceptibility and confirmed several previously reported risk loci . These results considerably increase our understanding of the genetic basis of SSc and shed light on the pathogenesis of the disease providing important information to discover new therapeutic targets genetically validated. Disclosure of Interest: None declared